Delayed Postoperative Spinal Cord Ischemia After Posterior Spinal Fusion in a Pediatric Patient with Syrinx and Decompressed Chiari: A Case Report. Issue 3 (21st July 2020) - Welling, Sebastian E.; Bauer, Jennifer M.
Abstract : Case: We present a case of delayed postoperative neurologic deficits 1 day after posterior spinal fusion in a pediatric patient with syrinx and previous Chiari decompression, which reversed with urgent rod removal. Conclusion: There is limited literature on delayed cord injury occurring after surgery in a patient with scoliosis of neuromuscular origin. Patients with syrinx and a history of Chiari decompression may have spinal cords more sensitive to injury including delayed ischemia after deformity treatment and should be paid extra perioperative attention including considering prolonged mean arterial pressure goals or more conservative deformity correction.